Bioactive triple peptide inhibits inflammasome activation to alleviate Salmonella-induced intestinal inflammation in mice via modulation of host defense and bacterial virulence. Issue 6 (5th March 2022) - Cui, Chenbin; Liu, Qi; Duan, Bingbing; Liu, Xiangchen; Wei, Hongkui; Peng, Jian
Abstract : Bioactive tripeptide inhibits inflammasome activation to alleviate S. typhimurium -induced inflammation via inhibiting the motility, adhesion, invasion and virulence gene expression of S. typhimurium . Abstract : Over the past years, Salmonella typhimurium has been considered an important pathogen that causes intestinal diseases and spells enormous economic shock to animal husbandry all over the world. Pyroptosis and inflammasome are involved in intestinal S. typhimurium infections. This study aims to explore the protective effects and potential mechanisms of a bioactive triple peptide (BTP) on S. typhimurium -induced intestinal infection. In this report, BTP exhibited anti-inflammatory and antibacterial activities in vivo ( S. typhimurium -infected C57BL/6 mice) and in vitro ( S. typhimurium -challenged THP-1 cells). We found that BTP significantly alleviated intestinal injuries and inflammation in S. typhimurium -infected mice. Besides, organ hypertrophy and bacteria translocation were improved effectively after BTP treatment. In macrophages, inflammasome activation caused by S. typhimurium infection was inhibited by BTP treatment. Of note, BTP significantly inhibited the adhesion and invasion of S. typhimurium to THP-1 cells. Moreover, the gene expressions of fljB and fliC were suppressed by BTP. All in all, our results suggest that BTP has the potential for alleviating S. typhimurium -induced inflammation.